Valor nutritivo de silagens de milho e aruana singulares e em consórcio - Gomes, Jackson Fernando (2015)
The consortium of corn fodder species is growing increasingly in Brazilian territory, this strategy is mainly used for reconstitution of pastures and soil cover. In this sense, the present work had as objective to evaluate the nutritional value of corn silages and aruana exclusive and in a consortium using the microsilos technique. The experimental design was of randomized blocks with five treatments (exclusive, unique corn spaced aruana 45 and 90 cm between rows and maize intercropping with aruana spaced the 45 and 90 cm between rows), being made three repetitions. Maize cv. Coodetec CD-308 was seeded in two spacing between rows (45 and 90 cm) seeking a population of 50 000 plants ha-1 on both systems simultaneously was seeded in the same area the Panicum maximum cv. Aruana IZ-5 in 45 cm spacing between rows the seeding density 10 kg ha-1. The collection of the material field was held when the grains of corn were with the milk line between one-third and two-thirds. Two cuts were carried out per plot, carried out at random in each treatment, with the help of four metal rods representing 1 m2. Later these samples were crushed with the help of heavy tractor and shredder. The crushed material was silage in silos of PVC (50 cm in length and 100 mm diameter). After 60 days, the material was being held desensilado the analysis of pH. Then, some of the material was transferred to the greenhouse, being dried and crushed and sent to the laboratory of food analysis for the determination of the values of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (FDA), mineral matter (MM) and TDN (NDT) of corn silage. The nutritional value of corn silage in consortium with aruana was similar to corn silage. The aruana grass silage exclusively presented lower nutritional value when compared to corn silage or grass in aruana. The spacing of sowing of the corn has not interfered in the nutritional value of silage.